2022
DOI: 10.1186/s12905-022-01610-7
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the implementation of a patient navigation program to improve breast and cervical cancer screening rates of Chinese immigrant women: a qualitative study

Abstract: Background Chinese Americans have lower breast and cervical cancer screening rates than the national average and experience multiple barriers to cancer care. Patient navigators have improved screening and follow-up rates for medically underserved populations, yet investigations of cancer navigation programs and their implementation among Chinese Americans are limited. To address this gap, we used the Consolidated Framework for Implementation Research (CFIR) to examine facilitators and barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Cultural perceptions, lack of adequate awareness, logistical challenges, and possible language barriers might be playing significant roles in these worrisome statistics. Reflecting our findings, other studies [ 39 , 40 ] emphasize the profound effect of linguistic and cultural barriers on breast and cervical cancer screening uptake, highlighting the necessity for culturally sensitive communication strategies to improve access. It is also possible that the benefits and existence of the free screening programs are not well-publicized or understood.…”
Section: Discussionsupporting
confidence: 81%
“…Cultural perceptions, lack of adequate awareness, logistical challenges, and possible language barriers might be playing significant roles in these worrisome statistics. Reflecting our findings, other studies [ 39 , 40 ] emphasize the profound effect of linguistic and cultural barriers on breast and cervical cancer screening uptake, highlighting the necessity for culturally sensitive communication strategies to improve access. It is also possible that the benefits and existence of the free screening programs are not well-publicized or understood.…”
Section: Discussionsupporting
confidence: 81%
“…Across these studies, five reported using technology other than email or telephone calls. This included Google Hangouts and WhatsApp, 95 an online patient navigation tool, 96 social media and phone applications, 97 Zoom, 98 and web‐based tool and video conferencing 99 . Four implementation and feasibility studies were also included 95,100–102 .…”
Section: Resultsmentioning
confidence: 99%
“…Common barriers reported included the inconvenience of in‐person support 136 ; limited experience using technology 95 ; hesitance to use a patient navigator 137 ; logistical‐related, psychological‐related, and knowledge‐related barriers 138 ; the lack of social support and culturally and linguistically concordant patient navigators 139 ; limited regular feedback to stakeholders 98 ; and institutional barriers 131 . Facilitators included interpretation services, pre‐prepared patients, high‐quality flexible services, and highly accessible patient navigators 98 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research focusing on health care delivery has revealed the complexity of coordinating care for people with cancer and proposes some promising interventions [ 54 , 55 ]. Recent studies and reviews on cancer care coordination interventions have found that patient navigation, designated care coordinators, and collaborative care models are among the common approaches implemented [ 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Multiple barriers to improving the provision of cancer care exist, including lack of social support, financial concerns, and problems with healthcare communications; in this context, effective care coordination is required [ 8 , 12 , 24 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Study Backgroundmentioning
confidence: 99%